More than just a dental practitioner: A realist evaluation of a dental anxiety service in Norway. (26th August 2021) - Bryne, Emilie; Hean, Sarah; Evensen, Kjersti; Bull, Vibeke
Abstract: Patients with dental phobia or a history of trauma tend to avoid dental services, which may, over time, lead to poor oral health. In Norway, a specific service targets these patients by providing exposure therapy to treat their fear of attendance and subsequently enable oral restoration. Dental practitioners deliver the exposure therapy, which requires a role change that deviates from their traditional practice. This paper explores how – and under what circumstances – dental practitioners manage this new role of alleviating dental anxiety for patients with a history of trauma or dental phobia. Using a realist evaluation approach, this paper develops theory describing which contexts promote mechanisms that allow practitioners to alleviate dental anxiety for patients with trauma or dental phobia. A multi‐method approach, comprising service documents (n = 13) and stakeholder interviews (n = 12), was applied. The data were then analysed through a content analysis and context‐mechanism‐outcome heuristic tool. Our findings reveal that dental practitioners must adopt roles that enable trust, a safe space, and gradual desensitisation of the patient to their fear triggers. Adopting these roles requires time and resources to develop practitioners' skills – enabling them to adopt an appropriate communication style and exposure pace for each patient.